Improved Gama Of Interferon (IFN- γ) Serum Levels And Decrease Due To Exposure Pulmonary Endotoxin Lipopolysaccharide (LPS) In Wood Dust Toward Workers Of Wood Processing Factory (International Journal of Scientific Research and Management (IJSRM), 2015)
The purpose of this study was to analyze the levels of IFN-γ blood serum and lung function decline due to exposure to endotoxin LPS in the wood dust on workers in the wood processing plant Surabaya, this kind of research is analytic observational prospective Longitudinal design. Population is all of the workers at the saw mill which consists of 30 workers, 11 workers study sample was determined by simple random sampling. Collecting technique is interview; dust and endotoxin measurements individually, blood sampling, and perform spirometry tests. IFN-γ levels and lung function measured at the time before and after work (cross-shift). Personal dust levels were measured using the Personal Dust Sampler (PDS) and endotoxin levels obtained from individual wood dust was measured using ELISA techniques and methods Lymulus Amebocyte Lysat (LAL) and lung function (FVC and FEV) is checked using a spirometer (Spirolab III) and levels IFNγ was assessed using fluorescence immunoassay I Chroma TM 1 Reader. Data analysis was performed using multiple linear regressions. The results showed levels of endotoxin LPS individuals have an effect on increasing blood serum IFN-γ 0.035, and decreased lung function (FVC) 0,040 and (FEV1) 0,028 (multiple regression test